Cryptococcal Meningitis and Tuberculous Meningitis Co-infection in HIV-Infected Ugandan Adults. (29th August 2018) - Ellis, Jayne; Cresswell, Fiona V; Joshua, Rhein; Kenneth, Ssebambulidde; Boulware, David R
Abstract: We report 5 HIV-infected Ugandan adults with cryptococcal and tuberculous (TB) meningitis co-infection. All unmasked meningitis occurred within 5 weeks of starting HIV therapy. Xpert MTB/RIF Ultra facilitated prompt diagnosis; however, 60% in-hospital mortality occurred. TB meningitis coinfection prevalence was 0.8% (5/586) among cryptococcal meningitis, 2 during second cryptococcal episodes.